Pengaruh Media Stimulasi Gambar Terhadap Kemampuan Membaca Siswa di Kelas II SD Negeri 105286 Tandam Hilir I - Ririn Safarina; Zon Saroha Ritonga; Rizka Hidayah Husin Lubis (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2022)
This study aims to: (1) Analyze the reading ability of second grade students before visual stimulation at SD Negeri 105286 Tandam Hilir I, (2) Test and analyze whether the visual stimulation method using image media affects the reading ability of second grade students at SDN 105286 Tandam Hilir I. This type of research is experimental research. The subjects of this study were the second grade students of SDN 105286 Tandam Hilir I, totaling 19 students. The method used in this research is the experimental method. The research design used was One Group Pretest-Posttes. In the trial activity did not use the control group. This design is done by comparing the results of the pretest with the posttest in the group being tested. The results of this study indicate that the process of observing and paying attention to students' images is able to improve reading skills. There is a difference in the pretest and posttest scores of class II students at SDN 105286 Tandam Hilir I.